Doppler ultrasound gating for adult cardiovascular magnetic resonance: Initial experience - Lucia D. Beissel; Fabian Kording; Christian Ruprecht; Alexander Isaak; Thomas M. Vollbrecht; Claus C. Pieper; Daniel Kuetting; Abdulamir Ali; Pia Wölfl; Christopher Hart; Julian A. Luetkens (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Despite being a common gating method for cardiovascular magnetic resonance (CMR), electrocardiogram (ECG) gating has its disadvantages, and new gating strategies are desirable. An alternative CMR gating method is Doppler ultrasound (DUS) gating, which detects blood flow and ventricular movement. The aim of this study was to prove the feasibility of DUS gating as a novel CMR gating method in a clinical patient population. Methods: In this prospective study, patients underwent clinically indicated CMR. Balanced steady-state free precession two-dimensional cine sequences in short-axis and 4-chamber views were acquired using ECG and DUS gating. DUS and ECG signal were recorded simultaneously. Time difference between R-wave and DUS systolic trigger detection was defined as trigger delay, the standard deviation of trigger delays as trigger jitter. Left and right ventricular parameters were assessed: left and right ventricular ejection fraction (LVEF, RVEF) and left and right ventricular end-diastolic volume index (LVEDVI, RVEDVI). Overall image quality was assessed using a 5-point Likert scale (5 = excellent to 1 = non-diagnostic). For statistical analysis, paired t-test, Wilcoxon test, Pearson correlation, and intraclass correlation coefficient (ICC) were employed. Results: Twenty-one patients (7 female) were included (age: 45.4 ± 19.7 years; body mass index: 27.6 ± 5.5 kg/m2). DUS mean trigger delay was 128 ± 28 ms. DUS mean trigger jitter was 23 ± 13 ms. Overall image quality showed no difference between ECG and DUS gating (e.g., short axis: 5 [interquartile range (IQR) 3–5] vs 4 [IQR 3.5–5]; P = 0.21). Quantitative analysis revealed no differences between ECG and DUS gating: LVEF (53.2 ± 9.2% vs 52.3 ± 9.1%; P = 0.18; ICC 0.97 [95% confidence interval [CI] 0.93–0.99]), LVEDVI (84.5 ± 15.8 mL/m2 vs 83.3 ± 15.8 mL/m2; P = 0.06; ICC 0.99 [95% CI 0.98–1.00]), RVEF (52.8 ± 8.0% vs 51.6 ± 7.2%; P = 0.06; ICC 0.96 [95% CI 0.89–0.99]), and RVEDVI (80.8 ± 17.6 mL/m2 vs 80.9 ± 16.5 mL/m2; P = 0.91; ICC 0.98 [95% CI 0.96–0.99]). In one patient with a prominent lingula of the lung image quality was non-diagnostic with DUS gating. Conclusion: CMR gating with DUS is feasible and can offer an equivalent performance to ECG regarding image quality and quantitative parameter assessment.